(untitled) (Third Sector Social Economic Review, 2025)
Nowadays, life insurance is used as a savings tool in addition to the protection it provides. With its pure insurance content, term life insurance includes replacing the income loss that will be caused by premature death and preventing the survivors from facing financial difficulties. Whole life insurance creates a source similar to retirement income in addition to death benefit. Single premium life insurance is an investment tool. The aim of the study is to reveal the nature and economic content of life insurance products, premiums paid for these insurances and finaly insurance payments, and thus to determine the valid approach and general practices for taxation. Premium payment for life insurance, return of savings element and insurance payments are interrelated. Therefore, the integrated structure of these stages has been taken into account in the examination and evaluation of the process throughout the study, and consistent and interrelated taxation rules have been determined. In addition, the taxation rules and possible effects of life insurance have been determined both absolutely and relatively by comparing them with similar instruments. In common practice, rules that take into account the mutual relationship of the stages of life insurance and provide tax convenience to life insurance by going beyond consistent taxation rules are preferred. There is a tax free inside buildup process for the returns on life insurance savings, and the returns are not taxed until they are distributed to the insured. Likewise, death benefits are commonly exempt from tax.